Factores asociados a estancia hospitalaria prolongada en pacientes con enfermedad cerebrovascular - Pacherres Inga, Dany David (2017)
Stroke hospitalizations are among the most expensive, and length of hospital stay is the major determinant of direct costs for stroke care. The aim of the study was to determine the factors associated with prolonged hospital stay (PHS) in patients with cerebrovascular disease (CVA). MATERIAL AND METHODS: A correlational descriptive study was carried out, in which 43 medical records of patients diagnosed with CVA hospitalized at the Trujillo Regional Teaching Hospital (TRTH) were reviewed during 2013. Factors such as age, gender, hospitalization service , Degree of dependency on admission (DDA), delay for in-hospital care, delayed tomography (CT), administration of medications in the first hour, presence of infection and / or comorbidities, and presence of comorbidities. Time of hospital stay. For the analysis of the data, the criteria independence test was used and value p <0.05. RESULTS: Factors such as hemorrhagic CVA, severe DDA and presence of infection and / or complication presented a statistically significant association with PHS (p = 0.0358, p = 0.0005 and p = 0.001, respectively). The average length of hospital stay found in this study was 6.1 days (SD: 4.14). The other factors evaluated did not present a statistically significant association with PHS. CONCLUSION: The factors associated with PHS in patients with CVA are the hemorrhagic type of CVA, severe DDA and the presence of infection and / or complications and that in the patients studied the length of hospital stay is not prolonged